Desain Antarmuka Pengguna Situs Web Alor Tours - Yosua Marthen Suryanto Mantaon; Jozua F Palandi; Rina Nurfitri (LPPM STIKI Malang, 2023)
Alor Regency is an island district located in East Nusa Tenggara Province which is bordered by the Flores Sea, Banda Sea, Ombai Strait, and Pantar Strait. Alor Regency consists of 3 large islands and 10 small inhabited islands. Geographically, the condition of this district is an archipelago and has high mountains surrounded by valleys and ravines. Alor Regency has many tourist attractions that are well known to the wider community, including marine tourism, cultural tourism, and historical tourism. Tourist attractions in Alor Regency are dominated by marine tourism in the form of beaches, islands, and marine parks. However, due to a lack of publication, its existence as a tourist area has not been fully explored. Another obstacle that stands in the way is the lack of tourism information that can be widely accessed. In this case, we need a media that can contain website-based tourist information about Alor Regency. Therefore